Formulation and evaluation of Lomefloxacin HCl as semisolid dosage forms - Almekhlafi, Sadik; Thabit, Anes A. M. (Journal of Chemical and Pharmaceutical Research, 2014)
The aim of this work was to formulate lomefloxacin HCl as a semisolid dosage form appropriate for topical dermatological application.Five empirical semisolid formulations were prepared with 1% drug strength in each. Three of those formulations contained hydrophilic bases (w/o cream , hydrophilic gel and a water soluble ointment) while the other two (simple ointment, lanolin ointment) were hydrophobic. The hydrophilic formulations showed better in vitro drug release than the hydrophobic ones. Among hydrophilic formulations, the cream and the water-soluble ointment showed excellent drug release. However, the ointment blank base showed antibacterial activity and was therefore excluded. For optimization of the drug strength in the cream formulation, the cream was reformulated so as to contain lower drug strength including(0.75, 0.5,0.2. & 0.125%)and their antibacterial activities were evaluated. The lowest effective strength of the drug in the prepared cream was 0.125%. Upon comparing with two commercial brands of topical antibacterials, lomefloxacin 0.125% cream formulation was be more potent and more effective antibacterial activity than those brands. Thespreadability, pH and of the cream formulation was accepted. Furthermore, theformulation caused no significant skin irritation on lab animals and its predicted isothermal shelf-life was quite long.